Adults with high functioning autism display idiosyncratic behavioral patterns, neural representations and connectivity of the 'Voice Area' while judging the appropriateness of emotional vocal reactions. (April 2020) - Pegado, Felipe; Hendriks, Michelle H.A.; Amelynck, Steffie; Daniels, Nicky; Steyaert, Jean; Boets, Bart; Op de Beeck, Hans
Abstract: Understanding others in everyday situations requires multiple types of information processing (visual, auditory, higher order…) which implicates the use of multiple neural circuits of the human brain. Here, using a multisensory paradigm we investigate one aspect of social understanding less explored in the literature: instead of focusing on the capacity to infer what a specific person is thinking, we explore here how people with high functioning autism (HFA) and matched controls with typical development (TD) infer the " population thinking ". For this we created an audio-visual 'social norm inference' task. Participants were required to imagine how most people would judge the appropriateness of vocal utterances in relation to different emotional visual contexts. Behavioral findings demonstrated that HFA individuals show more interindividual variability in these judgments despite equal within-participant reliability relative to TD. This was also the case for judgements of the valence of these vocalizations when presented in isolation. At the neural level, multivoxel pattern analysis of functional magnetic resonance imaging data revealed strikingly similar neural representations between HFA and TD participants at the group level across different hierarchical levels and neural systems. However, analyses at the individual-participant level revealed that the "Temporal Voice Area" (TVA) shows more interindividual variability in the HFA group, both for neural representations and functional connectivity. Thus, this larger neural idiosyncrasy in a high-level auditory area matches with the larger behavioral idiosyncrasy in HFA individuals, when judging auditory valence and its adequacy in different social scenarios. These results suggest that idiosyncrasy in task-relevant sensory areas in HFA participants could underlie their greater difficulties to estimate how others can think.